2019
DOI: 10.3390/molecules24244455
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Metabolic Effects of Chitosan and Chitosan Oligosaccharide on Epididymal WAT Browning and Thermogenesis in Obese Rats

Abstract: Many anti-obesity chemicals have been withdrawn from the market due to serious adverse reactions, and the researchers have turned their attention to low-toxic natural products. Previous studies have demonstrated that chitosan (CTS) and chitosan oligosaccharide (COS) were low-toxic natural products for the use of weight loss. However, it is still unclear whether CTS and COS have positive effects on the thermogenesis. In this study, CTS and COS significantly reduced the weight gain of rats without affecting food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 46 publications
1
14
0
1
Order By: Relevance
“…The main mechanism of action of chitosan in the body is to reduce the absorption of fat and cholesterol. Studies on obese mice have shown that chitosan activates the leptin signaling pathway (JAK2-STAT3), and thus reduces tissue resistance to leptin and inhibits adipogenesis (Wang et al, 2019b). Other studies have shown an increase in BAT and an increase in thermogenesis in obese rats fed a diet supplemented with chitosan (Pan et al, 2018).…”
Section: Chitosanmentioning
confidence: 99%
“…The main mechanism of action of chitosan in the body is to reduce the absorption of fat and cholesterol. Studies on obese mice have shown that chitosan activates the leptin signaling pathway (JAK2-STAT3), and thus reduces tissue resistance to leptin and inhibits adipogenesis (Wang et al, 2019b). Other studies have shown an increase in BAT and an increase in thermogenesis in obese rats fed a diet supplemented with chitosan (Pan et al, 2018).…”
Section: Chitosanmentioning
confidence: 99%
“…Therefore, increasing WAT browning and BAT thermogenesis are expected to be promising methods to prevent obesity. Wang et al found that COS reduced weight gain and serum lipid levels, and increased energy expenditure and brown fat content in HFD-induced obese rats [ 40 ]. Additionally, this study revealed that COS promoted WAT browning and BAT thermogenesis by upregulating the expressions of uncoupling protein 1 (UCP1), PRD1-BF1-RIZ1 homologous domain-containing 16 (PRDM16), and peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α) in these two types of adipose tissues through activating the p38 signaling pathway.…”
Section: Effect and Mechanism Of Cos On Metabolic Syndromementioning
confidence: 99%
“…Chitosan oligosaccharide combined with xanthine derivatives improved liver and kidney functions compared to pioglitazone, a standard antidiabetic drug [ 151 ]. Chitosan oligosaccharide also upregulated the expression of browning genes in white adipose tissues and thermogenesis of brown adipose tissues, which consequently reduced obesity in obese rats [ 152 ]. Chitosan oligosaccharide was applied in the form of tablet that had therapeutic effects on the regulation of serum lipid level and downregulation of cholesterol excretion genes including CYP7A1, LXR, PPAR-α, and LDLR in high fat diet-induced hyperlipidemic rats [ 153 ].…”
Section: Potential Applications Of Chitin and Chitosan Oligosacchamentioning
confidence: 99%